Surgical effects of nasal transposition of inferior rectus muscle – 135 cases of acquired superior oblique palsy - Okamoto, Mana (Clin Ophthalmol, 2015)
Nasal transposition of the inferior rectus (IR) muscle, which is transposed nasally with the insertion parallel to the spiral of Tillaux, could correct excyclotropia. However, as far as we are aware, there have been no reports examining the surgical effects of this procedure in multiple cases. Therefore, we examined the surgical effects of IR nasal transposition in 135 cases with acquired trochlear nerve palsy at Hyogo College of Medicine Hospital, Nishinomiya, Japan. One muscle width of IR nasal transposition corrected an average 5.6° in excyclotorsion, while bilateral IR nasal transposition corrected average 10.9°. This result shows this procedure is accurate quantitatively. Moreover, IR nasal transposition in combination with IR recession or resection can correct vertical deviation and excyclotorsion simultaneously. The results of this study suggest that IR nasal transposition should become first-line treatment for acquired superior oblique palsy.